ANALYSIS OF STUDENTS' ERROR IN SOLVING TRIGONOMETRY COMPARISON PROBLEMS WITH THE POLYA CRITERIA GUIDEN - ria maharani; Budi Murtiyasa (FKIP Universitas Muhammadiyah Tangerang, 2023)
Student mistakes in solving trigonometry problems have an impact on low student learning outcomes. This study aims to determine the percentage of student errors in solving trigonometry problems and describe the causes of these errors based on the Polya Criteria guidelines. This research is descriptive qualitative type. The subjects of this study were 35 students of class X.J SMA N 1 Wonosari. Data collection techniques used in this study were tests and interviews. The validity of the data is based on the triangulation process. Data analysis techniques in this study use data reduction techniques, data presentation, and drawing conclusions. Based on the results and discussion, it can be concluded that the students' mistakes in solving trigonometry problems with the Polya Criteria guide are as follows: 1) Understanding the problem (12.99%), 2) Developing a solution plan (30.30%), 3) Implementing a settlement plan (26.19%), 4) Checking again (30.52%). The causes of these errors, namely: students cannot understand the purpose of the questions given, students rarely solve problems by knowing, asking, answering, and concluding, students are confused about applying the trigonometry formula to solve problems, students are hasty and careless in solving problems, students are not used to it and feel no need to write conclusions at the end of the answer.Keywords: error, trigonometry, polya criteria